A meta-analysis comparing the composition and quality differences between chicken meats produced under the free-range and conventional systems. Issue 2 (3rd April 2022) - Davoodi, P.; Ehsani, A.; Vaez Torshizi, R.; Masoudi, A.A.
SUMMARY: Inconsistent results about the effects of free-range and conventional systems on economic carcase characteristics and the chemical composition of chicken meat have been reported. Free-range chicken meat has been presumably known as more nutritious and healthier than conventionally meat products so it has become highly present in the marketplace. In this study, due to an extensive systematic review plus meta-analysis, the effect of conventional and free-range rearing systems on meat quality and carcase traits has been evaluated based on thirty-nine included studies. A high level of heterogeneity was seen among studies, therefore, statistical analyses of random-effect models have been conducted to calculate summary statistics for the standardised effect size of the difference between free-range and conventional rearing systems. As a result, free-range significantly influenced abdominal fat yield, meat yellowness, protein and fat content of breast meat. However current meta-analysis showed that free-range had no significant negative effect on carcase weight, breast yield, leg yield, initial/ultimate pH, meat redness, cooking loss, drip loss, water holding capacity, and ash. In addition, two subset analyses according to sex (male, female and both sexes) and comparison type (slow-growing, fast-growing) clarified a part of sources of heterogeneity. Eventually, this study reported conclusive results that free-range significantly increased meat-related traits typically yellowness and protein of breast meat and conversely decreased abdominal fat yield and fat content of breast meat. In conclusion, free-range meat products can be characterised by different appearances due to the lower proportion of abdominal fat and yellower breast meat, also healthier and more nutritious because of lower fat concentration and higher protein content.